2016
DOI: 10.1038/nm.4141
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CBLB as a potential therapeutic approach for disseminated candidiasis

Abstract: Disseminated candidiasis has become one of the leading causes of hospital-acquired blood stream infections with high mobility and mortality. However, the molecular basis of host defense against disseminated candidiasis remains elusive, and treatment options are limited. Here, we report that the E3 ubiquitin ligase CBLB directs polyubiquitination of dectin-1 and -2, two key pattern recognition receptors for sensing Candida albicans, and their downstream kinase SYK, thus inhibiting dectin-1/2-mediated innate imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 49 publications
2
84
1
Order By: Relevance
“…We stimulated WT and Cblb −/− bone marrow–derived macrophages (BMDMs) with various TLR ligands and measured the production of TNF-α and IL-6 in cell culture supernatants. Consistent with recent published findings (Xiao et al, 2016; Yee and Hamerman, 2013), we detected no difference in the production of these pro-inflammatory cytokines by BMDMs generated from WT and Cblb −/− mice (Fig. 1 A).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We stimulated WT and Cblb −/− bone marrow–derived macrophages (BMDMs) with various TLR ligands and measured the production of TNF-α and IL-6 in cell culture supernatants. Consistent with recent published findings (Xiao et al, 2016; Yee and Hamerman, 2013), we detected no difference in the production of these pro-inflammatory cytokines by BMDMs generated from WT and Cblb −/− mice (Fig. 1 A).…”
Section: Resultssupporting
confidence: 93%
“…Therefore, the E3 ubiquitin ligase(s) specifically responsible for NLRP3 ubiquitination induced by NLRP3 inflammasome activators and the biological relevance of NLRP3 ubiquitination have not been fully characterized. Interestingly, although Cbl-b does not inhibit the signaling derived from TLRs (Xiao et al, 2016), we show here that it specifically inhibits IL-1β production by macrophages induced by canonical and noncanonical NLRP3 inflammasome stimuli. Therefore, we hypothesized that Cbl-b may be the E3 ubiquitin ligase that negatively regulates NLRP3.…”
Section: Introductionmentioning
confidence: 69%
“…A recent study demonstrated that inhibition of JNK1 promotes expression of CD23 (a recently discovered CLR), production for nitric oxide and a potent antifungal effect both in vitro and in vivo 117 . E3 ubiquitin ligase CBLB that ubiquitinates SYK, was shown to regulate antifungal immune responses downstream of dectin-1 and dectin-2 (Figure 3) 118,119 . Genetic deletion or peptide-based inhibition of CBLB promoted strong antifungal response, enhanced fungal killing and protected mice during systemic and cutaneous C. albicans infections 118 .…”
Section: Mucosal Immunity To Fungimentioning
confidence: 99%
“…As these CLRs lack a signaling domain, heterodimeric complexes signal via the ITAM-coupled adaptor FcRγ (9). Following fungal recognition, the E3 ubiquitin ligase CBLB ubiquitinates dectin-1, dectin-2, and SYK, targeting them for degradation (50)(51)(52). In systemic candidiasis, Cblb -/-mice exhibit reduced renal fungal burden and improved survival due to decreased inflammation-driven tissue damage (50)(51)(52).…”
Section: Introductionmentioning
confidence: 99%
“…Following fungal recognition, the E3 ubiquitin ligase CBLB ubiquitinates dectin-1, dectin-2, and SYK, targeting them for degradation (50)(51)(52). In systemic candidiasis, Cblb -/-mice exhibit reduced renal fungal burden and improved survival due to decreased inflammation-driven tissue damage (50)(51)(52). In contrast, TRIM62-mediated CARD9 ubiquitination is essential for BCL10 interactions, NF-κB activation, and defense against candidiasis (53).…”
Section: Introductionmentioning
confidence: 99%